Leverage nonclinical development of bispecifics by translational science. (September 2016) - Baumann, Andreas; Fischmann, Stephanie; Blaich, Guenter; Friedrich, Matthias
Highlights: Bispecific antibody constructs (bsAbs) may become key treatment option for serious diseases. BsAbs have unique formats that create new challenges for their development. Scientifically designed preclinical programs may inform positive clinical studies. BsAbs may provide a competitive advantage to companies. Abstract : Bispecific antibody constructs (Bispecifics, bsAbs) may have greater functionality compared to established monoclonal antibodies because they bind to 2 different targets or, potentially, to 2 epitopes on the same target (dual targeting). This may result in enhanced binding avidity with preferential binding to cells that express both targets or binding to targets on different cells. However, development of these next-generation biologics, including new formats, creates unique challenges due to their increased complexity. Here we review aspects of bsAbs preclinical development programs that may increase the success rates of bsAbs in clinical development.